Design and implementation of blue tooth aided inexpensive safety band for fishermen - Pradeep, Jayarama; Sridharan, S (International Journal of Engineering and Technology, 2018)
This paper presents with a new reliable inexpensive wireless health monitoring system designed for fishermen. Presently there are many smart devices available for the general population with many features in them that not put to use in every situation of our life. The most important aim of this paper is to deal with the safety and well-being of the fishermen during their voyage. The major cause of fishermenâ€™s poor health during voyage is due to lack of proper health guidance to the fishermen. This paper proposes with the monitoring of the fishermanâ€™s health through various sensors and relaying of those signals through blue tooth connectivity. The monitoring signals are finally obtained in Android mobile devices that can be used by the crew in real-time. The proposed approach is feasible for fishermen by establishing a software application to monitor the health of the fisherman. The proposed system is simple, economical and specifically designed for the people of the fishing community and it also enhances the motor control of the boat through the software interface by using a set of soft keys.Â Â